Explorando la inmunidad post-covid-19: Análisis de IgM e IgG en pacientes convalecientes del cercado de Lima - Soto, Katherine (2025)
Objective: This research aimed to analyse the behaviour of IgM and IgG antibodies in patients convalescing from SARS-CoV-2 in Cercado de Lima, focusing on factors such as age, sex, medical history and convalescence time.Materials and methods: Conducted as an observational and analytical study, prospective and longitudinal in nature, data were collected from 52 patients using the indirect ELISA technique at two different times.Results: Notably, almost all patients showed significant levels of IgG at both assessments, while IgM levels tended to decline over time. Notable variations in IgM decline were identified according to age and sex, being more accentuated in female individuals and younger age categories. On the other hand, variations in IgM response related to the patients' clinical history were observed. In the subsequent secondary assessment IgG ranges were markedly reduced in the proportion of patients with ranges greater than 100 IU/mL.Conclusions: IgM-Ac reactivity tends to decrease over time in convalescent SARS-CoV-2 patients, especially in females, younger age groups and patients with a certain clinical history. Notably, the IgG reaction decreases over time, suggesting that immunity may decrease in these patients over time. These findings raise crucial considerations for vaccination strategies and the understanding of natural immunity to the virus.